Development and validation of a gas chromatography-mass spectrometry method for determination of sterol oxidation products in edible oils. Issue 51 (6th May 2015) - Hu, Yinzhou; Yang, Guoliang; Huang, Weisu; Lai, Shiyun; Ren, Yiping; Huang, Baifen; Zhang, Liangxiao; Li, Peiwu; Lu, Baiyi
Abstract : An efficient GC-MS method for determination of sterol oxidation product profiles in edible oils was established by combination with optimized silylation, and validated using the standards of sitosterol oxidation products. Abstract : An efficient gas chromatography-mass spectrometry method was developed and validated for determination of sterol oxidation products (SOPs) in edible oils. The sample preparation involved cold saponification, liquid–liquid extraction, solid-phase extraction on a silica gel cartridge, and trimethylsilylation by N -methyl- N -(trimethylsilyl) heptafluorobutyramide with 5% 1-methyl imidazole. The trimethylsilyl ether derivatives of SOPs were separated by gas chromatography with a 30 m DB-5MS capillary column and quantified by a mass spectrometer in selective ion monitoring mode. 5α-Cholestane and 19-hydroxycholesterol were used as dual internal standards. The calibration curves for each compound showed correlation coefficients ( R 2 ) better than 0.98. The detection limits were below 12.9 ng mL −1 (except for epoxides). The intra- and inter-day determination precisions for diversiform SOPs were <10% in relative standard deviations; the recoveries ranged within 89.72% and 117.42%. The developed approach was successfully applied to study the presence of thirty-four different SOPs present at low levels in camellia, olive, sesame, peanut, rapeseed, rice bran, soybean and corn oils.